Blood-flow restricted resistance training in patients with sporadic inclusion body myositis: a randomized controlled trial. (3rd September 2018) - Jørgensen, AN; Aagaard, P; Frandsen, U; Boyle, E; Diederichsen, LP
Abstract : Objectives : To investigate the effect of 12 weeks of low-load blood-flow restricted resistance (BFR) training on self-reported and objective physical function, and maximal muscle strength in patients with sporadic inclusion body myositis (sIBM). Method : Twenty-two patients with sIBM were randomized into a training group (BFR group) or a non-exercising control group, according to CONsolidated Standards Of Reporting Trials (CONSORT) guidelines. The BFR group performed 12 weeks of BFR training twice per week. The primary outcome was the physical function domain of the 36-item Short Form Health Survey (pf-SF-36), which was used to measure self-reported physical function. All patients performed physical function tests (2-Minute Walk Test, Timed Up and Go, and 30-Second Chair Stand), completed the Inclusion Body Myositis Functional Rating Scale (IBMFRS), and were tested for isolated knee extensor muscle strength. Results : No effects of the training intervention were observed for pf-SF-36 or the objective physical function tests. Leg muscle strength decreased in controls (−9.2%, p = 0.02), but was unaltered in the BFR group (+0.9%, p = 0.87), resulting in a between-group difference in the per-protocol analysis (p = 0.026). Between-group differences in baseline to follow-up changes emerged for IBMFRS, in favour of the BFR group (p = 0.018). Conclusion : Twelve weeks of BFR training did not improve self-reported or objective physical function in these sIBM patients. However, the training protocol had a preventive (retaining) effect on the disease-related decline in leg muscle strength, which may aid the long-term preservation of physical function and postpone the need for healthcare assistance.